SURVEILLANCE OF WHITE SPOT SYNDROME VIRUS (WSSV) AND MYONECROSIS VIRUS (IMNV) INFECTIONS IN CULTURED Litopenaeus vannamei - Isti Koesharyani; Ariani Andayani; Ulfah Fayumi; Ketut Sugama (Indonesian Aquaculture Journal, 2019)
Disease surveillance programs will provide updated information on the distribution of diseases which allows proper development of mitigation and prevention strategies. WSSV and IMNV viruses are the most threatening diseases in shrimp and have affected the global shrimp farming industries. The present study was conducted to investigate the prevalence of WSSV and IMNV in three different locations of shrimp farms of South Sulawesi, West Nusa Tenggara and West Jawa. Samples of shrimp Litopenaeus vannamei were randomly collected from 20 active shrimp farms in the locations and five samples of postlarvae (PL) that were stocked in ponds. Tissue samples of the shrimp and whole body of PL were preserved in ethanol 90% for analysis. Determination of WSSV and IMNV were carried out by the mobile IQTM WSSV and IQTM IMNV Kit POCKIT Systems. The results showed that the prevalence of WSSV was 30% (6/20) and IMNV was 20% (4/20), while on PL was 40% (2/5). The result revealed that the South Sulawesi (Takalar) samples were positive only for WSSV while West Java (Panimbang) samples were positive only for IMNV. A follow-up study predicted that both viruses were transmitted from the PLs. The present study clearly confirmed that viruses were transmitted from PLs that were not free from either WSSV or IMNV. Therefore, a biosurveillance program is strongly recommended to be implemented in order to avoid the spread of the viral disease to other locations within Indonesia.